Challenges in pre-service teachers training: an analysis from their voices (Revista Internacional de Formação de Professores, 2016)
This article shows an analysis of the initial teacher training in the Education Degrees at the University of Extremadura. On it, the structure of the studies´plan of those degrees are described, according to the knowledge categories proposed by Shulman (1987), Marín Díaz (2004) and Koehler y Mishra (2006). In addition, it carries out a review of the organization and rules of the studies plan of European Higher Education Area. The text comprises a qualitative research which has collected different visions of both students and university teachers through interviews and discussion groups at the Faculty of Education. The data has been analyzed using the qualitative software NVIVO10 following a thematic criterion in accordance with the proposals of Plá (1999) and Yuste (2012) . After the results, there are evidences of the need of increasing a training based on competences and contextualized according to Goodwin y Kosnik (2013). At the same time, an excellent evaluation of the Practicum is appreciated , being the best result of the whole training programme.